Effects of condensed tannin fractions from Leucaena leucocephala (LAM.) De wit hybrid on methane mitigation, rumen fermentation and diversity of methanogens, protozoa and bacteria in vitro - Mookiah, Saminathan (2015)
Methane (CH4) emission is a primary environmental concern due to its contribution to global warming and climate change. Methane gas released from livestock, in particular the ruminants accounts to about one-third of global anthropogenic CH4 emission. Condensed tannins (CTs) are secondary plant metabolites that have shown methanogenic toxicity, resulting in reduced CH4 formation in ruminants. Condensed tannins are also known to bind proteins. The CTs produced by plants vary in molecular weights (MWs). The effects of CTs on protein-binding affinity and rumen methanogens may be dependent on the size of the CTs molecules. At the moment, it is not clearly understood whether CTs of different MWs would exert these effects differently. Thus, it was hypothesised that higher MWs, would be more efficient in binding protein and mitigating CH4 than CTs with lower MWs. Therefore, the objectives of the present study were to determine the effects of CT fractions of different MWs from a Leucaena leucocephala hybrid-Rendang (LLR) on protein binding affinity and CH4 mitigation by rumen microbes in vitro. In conjunction to these, the effects of CTs of different MWs on rumen microbial fermentation activities and microbial species were also determined. Condensed tannins were extracted from LLR and fractionated into five fractions (F1–F5) using size exclusion chromatography procedure. The degrees of polymerization (DP) of the CT fractions were measured by a modified vanillin assay, the MWs of the fractions were determined by Q-TOF LC/MS, and their structures were investigated using 13C-NMR. The protein-binding affinities of CT fractions were measured using a protein precipitation assay. The in vitro gas production test was used to investigate the effects of CT fractions on CH4 production, rumen microbial fermentation and populations (methanogens, protozoa and bacteria) in vitro. Based on the vanillin assay, it was found that the DP of the five CT fractions (fractions F1–F5) ranged from 4.86 to 1.56. The number-average MWs (Mn) of the different fractions were 1265.8, 1028.6, 652.2, 562.2, and 469.6 for fractions F1, F2, F3, F4, and F5, respectively. The 13C-NMR results showed that the CT fractions possessed monomer unit structural heterogeneity. The b values representing the CT quantities needed to bind half of the maximum precipitable bovine serum albumin increased with decreasing MWs from fraction F1 to fraction F5, with values of 0.216, 0.295, 0.359, 0.425, and 0.460, respectively. This indicated that higher MWs fractions had higher protein-binding affinity. The total gas [ml/g dry matter (DM)] and CH4 (ml/g DM) productions decreased significantly (P < 0.05) with increasing MWs of the CT fractions, with no significant reduction in DM digestibility. However, the in vitro nitrogen disappearance decreased significantly (P < 0.05) with the inclusion of CT fraction F1 (highest MW) when compared with the control (without CTs) and other fractions (F2–F5). The inclusion of CT fraction F1 also significantly (P < 0.05) decreased total volatile fatty acid, acetic acid concentrations and acetic/propionic acid ratio when compared with that of the control. The real-time PCR assay showed that higher MWs CT fractions (fractions F1 and F2) significantly (P < 0.05) decreased the total methanogens and methanogens from the order Methanobacteriales, and total protozoa than the lower MWs CT fractions (fractions F3-F5). Inclusion of higher MWs CT fractions F1 and F2 significantly (P < 0.05) increased the Fibrobacter succinogens population compared to CT fractions F3–F5. Whereas, inclusion of CT fractions (F1– F5) significantly (P < 0.05) decreased the Ruminococcus flavefaciens population compared with that of the control. Amplification of archaeal V3 regions of 16S rRNA genes using Illumina MiSeq sequencer showed that the relative abundance of the predominant unclassified Thermoplasmata-associated group (VadinCA11 gut group) increased significantly (P < 0.05), corresponding with increasing MWs of the CT fractions, whereas the predominant methanogen genus Methanobrevibacter was significantly (P < 0.05) decreased. The partial 18S rRNA gene analysis of the rumen protozoa using Illumina sequencer showed that the relative abundance of the predominant genus Entodinium significantly (P < 0.05) decreased with inclusion of CT fractions F1, F2 and F3 as compared with the control. In contrast, significant (P < 0.05) increases in second predominant rumen protozoa genus, Anoplodinium-Diplodinium were observed with CT fractions F1–F4 than that of the control. Illumina MiSeq sequencing of the V3 region of the bacterial 16S rRNA genes illustrated that the relative abundance of predominant genus Prevotella and unclassified Clostridiales were significantly (P < 0.05) decreased, corresponding with increasing MWs of CT fractions, whereas the cellulolytic bacteria Fibrobacter genus was significantly (P < 0.05) increased. In conclusion, CTs of different MWs have varying ability to bind proteins and decreased ruminal CH4 production by altering the populations and diversities of rumen methanogens and protozoa, and the effects were more pronounced for CTs with higher-MWs. The bacterial population and fermentation activities were also influenced by CT fractions, but the changes had no adverse effect on DM degradability. The strong binding affinity of higher MWs CTs to proteins may be beneficial in reducing degradation of feed protein by rumen microbes, thus enhancing bypass protein in ruminants. Moreover, higher MWs CTs could be potential methanogen inhibitors, which can be incorporated in ruminant diet to mitigate the CH4 emission, thus improving the feed efficiency and animal productivity, and at the same time reducing the contribution of ruminant livestock to global CH4 inventory.